Role of the tertiary and quaternary structure in the formation of bis-histidyl adducts in cold-adapted hemoglobins. - Balsamo A; Sannino F; Mazzarella L; MERLINO, ANTONELLO; PARRILLI, ERMENEGILDA; TUTINO, MARIA LUISA; VERGARA, ALESSANDRO (Biochimie, 2012)
All tetrameric hemoglobins from Antarctic fish, including that from Trematomus bernacchii, HbTb form in the ferric state, promptly and distinctively from all the other tetrameric hemoglobins, a mixture of aquo-met at the α subunits and bis-histidyl adduct (hemichrome) at the β subunits. The role of the tertiary and quaternary structure in the hemichrome formation is unknown. Here we report the cloning, expression, purification, spectroscopic and computational characterization of the β-chain of HbTb (β-HbTb). Similarly to the human β-chains, β-HbTb self-assembles to form the homotetramer β(4)-HbTb; however, the latter quantitatively forms reversible ferric and ferrous bis-histidyl adducts, which are only partially present in the human tetramer (β(4)-HbA). A molecular dynamics study of the isolated β subunit of the two Hbs indicates that the ability to form hemichrome is an intrinsic feature of the chain; moreover, the greater propensity of β-HbTb to form the bis-histidyl adduct is probably linked to the higher flexibility of the CD loop region. On the bases of these experimental and computational results on the isolated chain, the influence of the quaternary structure on the stability of the endogenous ferrous and ferric hexa-coordination is also discussed.